2016
DOI: 10.1038/srep28399
|View full text |Cite
|
Sign up to set email alerts
|

Protection against doxorubicin-induced myocardial dysfunction in mice by cardiac-specific expression of carboxyl terminus of hsp70-interacting protein

Abstract: Carboxyl terminus of Hsp70-interacting protein (CHIP) is a critical ubiquitin ligase/cochaperone to reduce cardiac oxidative stress, inflammation, cardiomyocyte apoptosis and autophage etc. However, it is unclear whether overexpression of CHIP in the heart would exert protective effects against DOX-induced cardiomyopathy. Cardiac-specific CHIP transgenic (CHIP-TG) mice and the wild-type (WT) littermates were treated with DOX or saline. DOX-induced cardiac atrophy, dysfunction, inflammation, oxidative stress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 55 publications
5
42
0
2
Order By: Relevance
“…The mechanisms of doxorubicin‐associated cardiac toxicity are not fully elucidated; however, cardiac cell apoptosis by ROS is a known side effect of doxorubicin. Multiple reports have demonstrated that doxorubicin‐induced cardiac toxicity is decreased by anti‐apoptotic methods in various animal models . It is known that ursolic acid protects the heart from ischaemic reperfusion injury or infarction by anti‐apoptotic activities .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of doxorubicin‐associated cardiac toxicity are not fully elucidated; however, cardiac cell apoptosis by ROS is a known side effect of doxorubicin. Multiple reports have demonstrated that doxorubicin‐induced cardiac toxicity is decreased by anti‐apoptotic methods in various animal models . It is known that ursolic acid protects the heart from ischaemic reperfusion injury or infarction by anti‐apoptotic activities .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple reports have demonstrated that doxorubicin-induced cardiac toxicity is decreased by anti-apoptotic methods in various animal models. [26][27][28] It is known that ursolic acid protects the heart from ischaemic reperfusion injury or infarction by anti-apoptotic activities. [29][30][31] Therefore, via anti-apoptosis, ursolic acid may decrease the side effects of doxorubicin on the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress could directly induce inflammatory cytokines expression, which was significantly increased after doxorubicin injection [37]. ACE2 prevented AngII-induced inflammatory response [38].…”
Section: Discussionmentioning
confidence: 99%
“…Interleukins (ILs) are a type of cytokine closely related to the inflammatory response. In previous studies, IL-1β was reported to be increased in the strong inflammatory response to DOX treatment in mice [ [6] , [7] , [8] , [9] ]. Other studies have demonstrated that ILs such as IL-10 and IL-33 could protect against DOX-induced cardiac injury [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%